Legal Responsibilities of Doctors in Terminating Life Assistance Therapy for Terminal Patients - Putra, Yudo Rastra Prasetiyo; Hufron, Hufron (Universitas PGRI Madiun, 2024)
Health law plays an important role in upholding basic rights in health services and maintaining a balance between the interests of patients and health workers. This research aims to examine whether doctors are allowed to stop life support therapy according to law using normative juridical legal research methods. The approaches used include statutory, conceptual and case approaches to test positive legal rules, legal principles and legal doctrine. The results of the analysis show that in the relationship between doctors and patients, patient autonomy in making medical decisions and effective communication are important aspects. Doctors have the responsibility to carry out medical procedures and treatment for patients who can no longer be cured, taking into account applicable legal principles. However, doctors are prohibited from carrying out euthanasia, whether active or passive, in accordance with the medical code of ethics and the Hippocratic oath. In discontinuing life support therapy, doctors must ensure that the action is in accordance with applicable medical and legal perspectives, and minimizes the risk of violating the law.